Cadmium targeting transcription factor EB to inhibit autophagy-lysosome function contributes to acute kidney injury - Peng-Fei Dong; Tian-Bin Liu; Kai Chen; Dan Li; Yue Li; Cai-Yu Lian; Zhen-Yong Wang; Lin Wang (Journal of Advanced Research)
Introduction: Environmental and occupational exposure to cadmium (Cd) has been shown to cause acute kidney injury (AKI). Previous studies have demonstrated that autophagy inhibition and lysosomal dysfunction are important mechanisms of Cd-induced AKI. Objectives: Transcription factor EB (TFEB) is a critical transcription regulator that modulates autophagy-lysosome function, but its role in Cd-induced AKI is yet to be elucidated. Thus, in vivo and in vitro studies were conducted to clarify this issue. Methods and results: Data firstly showed that reduced TFEB expression and nuclear translocation were evident in Cd-induced AKI models, accompanied by autophagy-lysosome dysfunction. Pharmacological and genetic activation of TFEB improved Cd-induced AKI via alleviating autophagy inhibition and lysosomal dysfunction, whereas Tfeb knockdown further aggravated this phenomenon, suggesting the key role of TFEB in Cd-induced AKI by regulating autophagy. Mechanistically, Cd activated mechanistic target of rapamycin complex 1 (mTORC1) to enhance TFEB phosphorylation and thereby inhibiting TFEB nuclear translocation. Cd also activated chromosome region maintenance 1 (CRM1) to promote TFEB nuclear export. Meanwhile, Cd activated general control non-repressed protein 5 (GCN5) to enhance nuclear TFEB acetylation, resulting in the decreased TFEB transcriptional activity. Moreover, inhibition of CRM1 or GCN5 alleviated Cd-induced AKI by enhancing TFEB activity, respectively. Conclusion: In summary, these findings reveal that TFEB phosphorylation, nuclear export and acetylation independently suppress TFEB activity to cause Cd-induced AKI via regulating autophagy-lysosome function, suggesting that TFEB activation might be a promising treatment strategy for Cd-induced AKI.